TINGKAT RISIKO PUTUS SEKOLAH PADA REMAJA DI PROVINSI PAPUA TAHUN 2018 - Rintan Auliyah Rahma; I Made Arcana (Politeknik Statistika STIS, 2020)
The compulsory education program has been implemented since 1994. However, the mean years of schooling of youth in Papua Province is still below the national figure and is the lowest mean years of schooling in Indonesia. Meanwhile, the rate of continuing to high school in Papua Province is also the lowest order and has a gap that is quite far compared to West Papua Province. Youth should be or have completed 12 years of compulsory education. However, the low rate of continuing to high school indicates that there are youth who have dropped out of school. The incidence of dropping out of school will encourage youth to enter the job market early. By using survival analysis, this study aims to determine the socio-demographic background of youth who have dropped out of school. Youth who come from poor households status have the highest risk of dropping out of school. Youth with household heads who work in informal sector and unemployment household heads have a higher risks to not complete education, than household heads who work in formal sector.